Effect of Indole Butyric Acid (IBA) Application and Spliced Grafting on the Growth of Garuda Clone Cassava - Menis Triana; Yusnita Yusnita; Setyo Dwi Utomo; Dwi Hapsoro; Fitri Yelli (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Increasing cassava production is required to maintain supply sustainability and meet seed demand. The use of splice grafting and the application of auxin IBA are expected to accelerate rooting and enhance the productivity of cassava. The objective of this research is to study the effect of IBA application on the growth of cuttings and grafted seedlings of cassava. The research was conducted from October 2024 to February 2025 at the Integrated Field Laboratory of the Faculty of Agriculture, University of Lampung, Natar District, South Lampung. The experiment was designed according to randomized block design (RBD) with factorial treatments arrangement (3×2). The first factor was IBA concentration consisted of three levels, namely without IBA (A0), 1000 ppm (A1), and 2000 ppm IBA (A2). The second factor consisted of 2 types of plant materials, namely cuttings seedlings (B1) and slanted graft seedlings (B2). The results show that the application of IBA significantly increases the growth and production of cassava compared to without IBA application. IBA at 2000 ppm is the best concentration for the observed variables. The use of planting materials, whether cuttings or slanted grafts, both enhance the yield of cassava.